Credit Risk Transfer: To Sell or to Insure - James R. Thompson (Queen's University, Department of Economics, 2007)
This paper analyzes credit risk transfer in banking. Specifically, we model loan sales and loan insurance (e.g. credit default swaps) as the two instruments of risk transfer. Recent empirical evidence suggests that the adverse selection problem is as relevant in loan insurance as it is in loan sales. Contrary to previous literature, this paper allows for informational asymmetries in both markets. We show how credit risk transfer can achieve optimal investment and minimize the social costs associated with excess risk taking by a bank. Furthermore, we find that no separation of loan types can occur in equilibrium. Our results show that a well capitalized bank will tend to use loan insurance regardless of loan quality in the presence of moral hazard and relationship banking costs of loan sales. Finally, we show that a poorly capitalized bank may be forced into the loan sales market, even in the presence of possibly significant relationship and moral hazard costs that can depress the selling price.
Keywords: G21; G22; D82; 330; credit risk transfer; banking; loan sales; loan insurance; credit derivatives; Bankgeschäft; Kreditrisiko; Kreditversicherung; Verkauf; Adverse Selektion; Theorie